2021
DOI: 10.3390/antibiotics10121434
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Methicillin-Resistant Staphylococcus aureus Nares Screening in Hospitalized Children with Acute Infectious Disease Syndromes

Abstract: Studies in adults support the use of a negative methicillin-resistant Staphylococcus aureus (MRSA) nares screening (MNS) to help limit empiric anti-MRSA antibiotic therapy. We aimed to evaluate the use of MNS for anti-MRSA antibiotic de-escalation in hospitalized children (<18 years). Records of patients admitted between 1 January 2015 and 31 December 2020 with a presumed infectious diagnosis who were started on anti-MRSA antibiotics, had a PCR-based MNS, and a clinical culture performed were retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…A study conducted at another children’s hospital in New York also reported a high NPV of 95.5% and a low PPV of 42.9% for all indications combined. 10 Of note, this cohort study utilized PCR-based MNS. PCR-based MNS tests were excluded in our study due to low utilization during the study period as our institution transitioned to preferentially utilizing PCR-based MNS in the last few months of the study period.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted at another children’s hospital in New York also reported a high NPV of 95.5% and a low PPV of 42.9% for all indications combined. 10 Of note, this cohort study utilized PCR-based MNS. PCR-based MNS tests were excluded in our study due to low utilization during the study period as our institution transitioned to preferentially utilizing PCR-based MNS in the last few months of the study period.…”
Section: Discussionmentioning
confidence: 99%
“…1 Their key finding of a high negative predictive value (NPV) (95%) of MNS for all combined indications adds to 2 previously and 1 since published studies in children confirming high NPVs (95.5%-100%) for infections that primarily included lower respiratory tract infections (LRTI) and skin and soft tissue infections (SSTI). [2][3][4][5] We applaud Braga for being able to calculate the first-time infection-specific NPVs of MNS in children with LRTIs [95% (n = 46)], SSTIs [96% (n = 24)] and bone and joint infections (BJIs) [91% (n = 22)]. We concur with their conclusions that MNS in children may have a utility beyond LRTIs including SSTIs and BJIs as well as with their call for more data specifically for those 2 latter infections.…”
Section: What About Hospitalized Children With Osteomyelitis?mentioning
confidence: 99%
“…This work represents a subanalysis of our group's endeavor since 2015 to evaluate SNS's utility in hospitalized children, which has been approved by our institutional review board and its results in part previously reported. 3 We included 36 patients with a median age (range) of 8.5 years (0-19). Thirty-two (88.9%) were started on empiric anti-MRSA antibiotics, most on clindamycin (n = 21, 58.3%), vancomycin (n = 8, 22.2%), or both (n = 2, 5.6%).…”
Section: What About Hospitalized Children With Osteomyelitis?mentioning
confidence: 99%
See 2 more Smart Citations